DETERMINANTS OF INVESTMENT INTEREST IN INDONESIA: EXAMINING THE INTERACTION EFFECTS OF GENDER - Kalista, Apriwina Yulita; Wendy, Wendy; Giriati, Giriati; Mustika, Uray Ndaru; Mustaruddin, Mustaruddin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The active use of social media by young people and their predominance in Indonesian investment in capital markets between 2021 and 2024 suggest an interesting trend that deserves more investigation. Having a focus on the impact of social media influencers, the Fear of Missing Out (FoMO) phenomenon, and the significance of financial literacy in fostering investment interest, this study attempts to pinpoint and examine the elements that motivate the younger generation to pursue investing. Primary data from surveys is used in this quantitative study. MRA using SPSS software version 25 was used to test the interaction effect. It has been demonstrated that financial literacy, fear of missing out (FoMO), and social media influencers all have a favorable impact on investing interest. The relationship between genders